Frequency-Based Control Strategy for Compact Electromagnetic Tuned Mass Damper. (4th May 2021) - Kopylov, Semen; Chen, Zhaobo; Abdelkareem, Mohamed A. A.
Abstract : The control of harmonic machine-induced vibration has been a common task in the engineering scope. The passive tuned mass dampers represent the most reliable and practical approach to reduce such excessive vibration. Additionally, different control strategies can be implemented on TMDs to improve the attenuation performance further. However, most of the proposed control strategies for TMDs represent cost and complex systems with many sensors, which hinders the broad implementation. In this paper, the frequency-based semiactive control (FBC) strategy was proposed for an electromagnetic tuned mass damper (ETMD). The concept of a controllable system with switched transistor was utilized for the proposed control strategy. The proposed control policy's effectiveness was validated by experimental results, where the controlled ETMD was applied on a protected mass test bench. This paper concluded that the proposed control strategy has a significant advantage over the passive TMD. The reduction of 14% of the excessive harmonic vibration for the protected structure was observed.